Using US Tuning to effect: The American Historical Association's Tuning Project and the first year research paper. (October 2017) - Belanger, Elizabeth
While research has long been recognized as a high impact practice in undergraduate education, much of the scholarship on undergraduate research has focused on students in the final years of their degree. This article describes a study of the ability of first year students to undertake historical research in an introductory level course at a small liberal arts college. It discusses the challenges that first year student's face in interpreting primary sources, working with multiple sources and crafting arguments based narratives about their findings. It also documents how a research paper assignment advances students' historical thinking skills and contribute to the development of what the American Historical Association has termed the "core competencies" in the discipline.